A LOCAL GOVERNMENT IN EUROPEAN COUNTRIES, SPECIAL CHARACTERISTICS OF THE FORMS AND STRUCTURES - Teki Kurti (European Scientific Journal, ESJ, 2014)
The territorial organization of governing in the “unitary state”, “federal state”, “confederation”, with their constituent units is another aspect of the functioning of governing, which shows the government allocation. The above mentioned types are distinguished by the governing ratio in the territorial integrity of the nation-state, which in the governing system of liberal democracy are known as “central governing” and “local governing” followed by the attributes of “centralization”, “decentralization” , “self-governing” or “local autonomy”. It observes the basic functioning of the system, the creation and realization of the relations between the government and the governed, through which are implemented the basic principles of: - participation in governance; -expression of the will and liking of governing; - fulfilment of tasks of governing according to the interests and aspirations of the governed; - responsibility and accountability of the government. The effectiveness of the government, assessed through the fulfilment of tasks with concrete results related to the fulfilment of the interests of the entire nation and society, is another important aspect in the system of governing.